EFEK TENS DAN TERAPI LATIHAN TERHADAP KEMAMPUAN FUNGSIONAL PADA KASUS OSTEOARTHRITIS LUTUT : Literature Review - Dinnur Fajriantama (2020)
Functional ability is the ability that has the greatest influence in daily activities. Osteoarthritis is a condition where the bones experience decreased limb function which causes a person to be hampered in his ability to perform daily activities. To avoid the decline in functional abilities caused by osteoarthritis, the need for physiotherapy interventions is one of them by using TENS (Trancutaneus Electrical Nerve Stimulation) and the provision of exercise therapy. The critical success parameter of the intervention is by using the WOMAC (Western Ontario and McMaster Index). In the literature study conducted this time aims to determine the effectiveness of the use of TENS (Transcutaneus Electrical Nerve Stimulation) and exercise therapy in OA patients. The method used is in the form of a literature study using 4 articles sourced from Google Scholar. Where to determine the quality of the journal using the PEDro Scale (The Physiotherapy Evidence Database rating scale). After synthesis and extraction of data, it was found that the administration of TENS and exercise therapy could be used as a physiotherapy planning program to improve functional abilities in people with OA.